Analisis Kendala dan Solusi Implementasi Kurikulum Merdeka di SDN 15 Ulu Gadut - Novitasari, Sefty; Indah Permata Sari; Hasa Putri Herliza; Salma Rahmadani; Silvia Rahma Sari; Fira Siska Aulia; Reinita (STKIP Subang, 2026)
The Independent Curriculum is one of the latest innovations in Indonesia’s education system, aimed at making learning more flexible and student-centered through a deep learning approach that emphasizes a thorough understanding of ideas. However, when implemented in elementary schools, teachers and institutions face many challenges.The purpose of this study is to identify various problems that arise as a result of implementing the Independent Curriculum in elementary schools and to propose alternative solutions to these issues. This research employs a qualitative descriptive method through a literature study. It examines books, scientific journals, educational articles, and official documents related to curriculum policies.The results show that several major challenges hinder the implementation of the Independent Curriculum, including the increased administrative workload for teachers, difficulties in developing teaching materials, and limited school facilities and infrastructure. To address these issues, various efforts are needed, such as teacher training, improved collaboration among teachers, better management of facilities and infrastructure, and simplification of learning administration.